The development of a valid and reliable nutrition knowledge questionnaire and performance-rating scale for urban South African adolescents participating in the 'Birth-to-Twenty' study - Whati, Lindiwe Harriet (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2005.